Polypoidal Choroidal Vasculopathy - Mirza Metita; Yorihisa Kitagawa; Hiroyuki Shimada; Hiroyuki Nakashizuka (Indonesian Vitreoretinal Society, 2018)
Introduction: to report a case of PCV that has been successfully treated with intravitreal injection of t-PA, ranibizumab, and pneumatic displacement. Method: A 65 years old man presented with blurred vision of his right eye. No systemic abnormalities were found. Initial visual acuity RE was 6/18. Funduscopy examination showed submacular hemorrhage in posterior pole. OCTA, FA and ICG confirmed the diagnosis of PCV. We performed anterior chamber paracentesis and intravitreal injection of 0,05 ml t-PA, 0,05 ml ranibizumab, and 0,3 ml 100% C3F8 at a time in retrobulbar anesthesia. The patient was instructed to maintain face down positioning for 2 days. Results: We evaluated the visual acuity, central retinal thickness (CRT), and central pigment epithelial detachment (PED) thickness for 2 years. The visual acuity was increasing gradually from 6/18 to 6/6 in the first year. The hemorrhage was displaced completely, the CRT and central PED thickness were decreased. In the second year the patient had recurrence of PCV with serous retinal detachment and treated with intravitreal aflibercept. Conclusion: Combined treatment of intravitreal t-PA, ranibizumab, and C3F8 can be used as a beneficial therapy for PCV.